40 acres [videorecording (DVD)] - Deadwyler, Danielle; O'Connor, Kataem; Greyeyes, Michael (Magnolia Pictures, 2025)
In a post-apocalyptic world with food scarcity, a Black family of Canadian farmers descended from American Civil War migrants defend their homestead against cannibals trying to seize their resources.